2017
DOI: 10.1590/1806-9282.63.09.779
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anemia and body mass index (BMI) on neuromotor development of preschool children

Abstract: Objective: According to data from the World Health Organization (WHO), anemia is a prevalent health problem that leads to increased morbidity and mortality, especially in preschool children. Anemia is recognized as a major health problem due to its negative effects on the mental and physical development during childhood. The aim of our study was to determine the levels of anemia of children in a kindergarten affiliated to the Directorate of National Education using a non-invasive method, and to investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Numerous previous studies have found higher prevalence of iron deficiency in obese children. [28][29][30][31][32][33][34][35] Our findings show a lower level of serum iron and lower transferrin saturation in obese children than normal weight but do not reveal a significant deficiency of iron in obese children.…”
Section: Discussionmentioning
confidence: 74%
“…Numerous previous studies have found higher prevalence of iron deficiency in obese children. [28][29][30][31][32][33][34][35] Our findings show a lower level of serum iron and lower transferrin saturation in obese children than normal weight but do not reveal a significant deficiency of iron in obese children.…”
Section: Discussionmentioning
confidence: 74%
“…Children under the age of five are particularly at risk because of the rapid growth and development [5]. The prevalence of anemia worldwide is between 22.9-26.7% [1]. In our study; after migrants and those with chronic diseases were excluded, of the 5089 patients who applied to our outpatient clinic 22% had anemia.…”
Section: Discussionmentioning
confidence: 76%
“…Anemia is an important global public health problem that shows the socio-economic development of every nation and individual. The incidence of anemia worldwide is between 22.9-26.7%.The prevalence is over 40% in Turkey [1]. anemia is evaluated according to the mean erythrocyte volume (MCV) in three main headings: microcytic, macrocytic and normocytic anemia [2].…”
Section: Introductionmentioning
confidence: 99%